The European consumer’s dilemma: "Excessive paternalism" or individual autonomy - Añoveros Terradas, Beatriz (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This paper analyzes the different methods (multilateral and unilateral) used by European private international law to protect the consumer and, in particular, their potential cumulative application, i.e. the potential incidence of national consumer protection rules (whose origin lies in the implementation of European directives) as overriding mandatory provisions in consumer contracts covered by a special choice of law rule protecting the consumer. The relationship Art. 6 RRI and Art. 9 RRI has been widely discussed, both with regard to contracts covered by Art. 6 RRI and to those excluded from it (active consumers and express exclusions). With regard to the former, the cumulative application of both methods could lead to an “excessive paternalism” that goes against party autonomy and the Rome I Regulation objectives, and is therefore unacceptable in intra-European consumer relations. In situations linked to third States (extra-European), such double protection will sometimes be necessary to guarantee the European level of protection.
Keywords: Overriding mandatory provisions; Art 6 Rome I Regulation; Consumer Protection Directives